Considerations in Free Flap Reconstruction of the Midface - Hammer, Daniel; Vincent, Aurora G.; Williams, Fayette; Ducic, Yadranko (Facial Plastic Surgery, 2021)
Midface reconstruction has been a consistent challenge for reconstructive surgeons even with the significant advances in technology and technique achieved over the recent years. A meticulous preoperative assessment of the patient is required to properly assess the defect or anticipated defect, determine proper reconstructive surgical plan, and discuss expected functional and aesthetic outcomes with the patient. For years we have employed local flaps, regional flaps, obturators, alloplastic implants, free flaps, or a combination of the previously mentioned techniques to address complex midface reconstruction. Free flap reconstruction in the midface requires special considerations for the pedicle, flap selection, and flap design to ensure an optimal outcome. The introduction of virtual surgical planning for reconstruction has enhanced patient outcomes to include advances in immediate dental rehabilitation at the time of free flap surgery. Postoperative considerations including quality of life, functional and aesthetic outcomes, and management of complications will also be discussed.
Keywords: midface reconstruction; free flap; maxillary obturator; orbit reconstruction; dental rehabilitation